Morphological characteristics and genome-wide association analysis among local Andrographis paniculata from Thailand under controlled environment in plant factory - Praderm Wanichananan; Supattana Janta; Suchalee Sueachuen; Tanawut Chiangklang; Kriengkrai Mosaleeyanon; Siripar Korinsak; Clive Terence Darwell; Panita Chutimanukul (PLoS ONE, 2025)
Andrographis paniculata Wall. ex Nees (A. paniculata) is a medicinal plant widely used in Southeast Asian traditional medicine. Plant factories with artificial lighting (PFAL) provide controlled environments for optimizing plant growth and quality. However, the variability in biomass and bioactive compound production among A. paniculata varieties cultivated in PFAL is not well understood. This study investigated ten locals of A. paniculata accessions to assess their growth characteristics and andrographolide (AP1) content in a PFAL system using hydroponic cultivation. Among the accessions, the TTT cultivar showed significantly higher stem height, plant width, above-ground biomass yield, leaf number, and AP1 content compared to others. Phylogenetic analyses based on SNP markers revealed that TTT is morphologically distinct but genetically similar to CR, RB, PL, and PC accessions. A genome-wide association study (GWAS) identified two significant SNP regions on chromosome 9 associated with yield and AP1 content. These findings highlight the potential of TTT as a high-quality cultivar for pharmaceutical use and provide insights into key genes that could be targeted for breeding programs to improve Andrographis production in PFAL systems.